Hábitos alimentarios, entrega de hierro, estado nutricional y hemoglobina en niños de la I.E.I.P.S.M n° 601491 Madre Teresa de Calcuta - Alvarado Ampudia, Anita (2023)
This research entitled Eating habits, iron delivery, nutritional status and hemoglobin in children of the I.E.I.P.S.M. N°601491 - Mother Teresa of Calcutta, aimed to determine the relationship of eating habits, iron delivery with nutritional status and hemoglobin level in children of 3 and 4 years. The study has a non-experimental quantitative approach, and has a cross-sectional correlational descriptive design. The sample used in the study consisted of 134 boys and girls between the ages of 3 and 4 years; 62 female and 72 male. Evaluation of the hemoglobin level and anthropometric measurements were carried out at the institution. The eating habits survey, for its part, was distributed to parents and/or guardians through the director and teachers. In relation to the indicators of nutritional status, the weight/age (W/E) of the majority of the boys and girls was within the normal range, with 98%. Only 1% were malnourished and overweight. Regarding the weight/height (P/T) indicator, 99% of the boys and girls presented a normal state, while only 1% presented childhood obesity. In the height/age (T/E) indicator, 100% of the boys and 99% of the girls presented a normal state. Regarding hemoglobin levels, 12% of the children presented mild anemia and 5% moderate anemia. It is highlighted that 27% of the children had hemoglobin values between 11.0 and 11.5 mg/dl, which indicates a risk range for suffering from anemia. Regarding the delivery of iron supplements, only 52% of boys and girls received any type of supplement. Regarding the source of delivery of iron supplements, only 20% and 26% were provided by health institutions, while 54% were provided by other public or private institutions. There is a significant correlation between eating habits with nutritional status and iron delivery with the hemoglobin level in 3 and 4 year old children of the I.E.I.P.S.M. N°601491 - Mother Teresa of Calcutta.